2016
DOI: 10.1159/000446321
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Multifocal Electroretinography in the Assessment of Drug-Induced Retinopathy: A Review of the Literature

Abstract: Multifocal electroretinography (mfERG) is an objective, noninvasive examination for the assessment of visual function. It enables the stimulation of multiple retinal areas simultaneously and recording of each response independently, providing a topographic measure of retinal electrophysiological activity in the central 40-50° of the retina. A clinical application of mfERG represents the assessment of retinal toxicity associated with systemic medications. Drug-induced retinopathy represents a disease that, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 82 publications
0
25
0
1
Order By: Relevance
“…mfERG is a useful tool for detecting various retinal abnormalities that are not obvious in fundus examination 16–18. Initially, our patient showed slight anatomical disturbance in fundus examination and OCT, however, mfERG a month later identified significant abnormalities in macular function.…”
Section: Discussionmentioning
confidence: 70%
“…mfERG is a useful tool for detecting various retinal abnormalities that are not obvious in fundus examination 16–18. Initially, our patient showed slight anatomical disturbance in fundus examination and OCT, however, mfERG a month later identified significant abnormalities in macular function.…”
Section: Discussionmentioning
confidence: 70%
“…It has been shown that in all types of maculopathy there is a decrease or loss of central electrical response, which is related to the degree and extent of the lesion. MfERG is a valuable method particularly in cases where the patient is visually asymptomatic, visual acuity is normal and macular lesions are not clearly visible ophthalmoscopically [ 31 ]. MfERG reflects the electrophysiological responses mainly from the inner retinal layers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Medications commonly known to produce retinal toxicity include chloroquine and hydroxychloroquine, vigabatrin, deferoxamine, ethambutol, interferon-α, tamoxifen, digoxin, sildenafil, canthaxanthin, aminoglycosides, and amiodarone. [ 6 7 ]…”
Section: Discussionmentioning
confidence: 99%